Demographic Transition and Economic Growth in Indonesia - Endang Rostiana; Anggia Rodesbi (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2020)
Abstract: Demographic transition in Indonesia indicated by an increase in the productive age population, a decrease in the unproductive age population, and leads to a decrease in the dependency ratio. This study analyzes the relationship between demographic transition and Indonesia's economic growth. If the population structure changes contribute positively to economic development, it means that Indonesia has enjoyed a bonus from their demographic transition. The analysis used was multiple regression, with economic growth rate as dependent variable and population growth rate, capital, young age dependency ratio and old age dependency ratio as independent variables. This study has found that the demographic transition, represented by growth of young age dependency ratio, growth of capital, and economic crisis dummy variable partially contributes positively to economic growth. It can be concluded that the demographic transition in Indonesia provides a bonus that is in the form of a positive contribution to economic growth. Keywords: economic growth, capital, population, dependency ratio Transisi Demografi dan Pertumbuhan Ekonomi Indonesia Abstrak: Transisi demografi di Indonesia ditandai dengan penurunan tingkat fertilitas dan mortalitas, yang berdampak pada peningkatan persentase penduduk usia produktif dan penurunan persentase penduduk usia tidak produktif. Hal ini menyebabkan angka beban tanggungan menjadi semakin kecil. Penelitian ini bertujuan untuk menganalisis hubungan transisi demografi dengan pertumbuhan ekonomi Indonesia. Jika transisi demografi berkontribusi positif pada pertumbuhan ekonomi, maka dapat dikatakan Indonesia telah menikmati bonus demografi. Model analisis menggunakan persamaan regresi, dengan pertumbuhan ekonomi sebagai variabel terikat. Variabel bebasnya adalah pertumbuhan penduduk, pertumbuhan modal, pertumbuhan dependency ratio penduduk usia muda, dan pertumbuhan dependency ratio penduduk usia lanjut. Hasil regresi menunjukkan bahwa transisi demografi yang diwakili oleh pertumbuhan dependency ratio penduduk usia muda, pertumbuhan modal, dan variabel dummy krisis ekonomi secara parsial berpengaruh positif terhadap perumbuhan ekonomi Indonesia. Hasil tersebut dapat disimpulkan bahwa transisi demografi memberikan bonus berupa kontribusi positif terhadap pertumbuhan ekonomi di Indonesia. Kata kunci: pertumbuhan ekonomi, modal, penduduk, dependency ratio